Comparison of discrete-time sliding mode control algorithms for seismic control of buildings with magnetorheological fluid dampers. (April 2023) - Kemerli, Muaz; Şahin, Özge; Yazıcı, İrfan and Çağlar, Naci and Engin, Tahsin
Semi-active control implementations for structures are gaining considerable attention in civil engineering. This paper presents a method for the design and implementation of the discrete-time sliding mode controller with a hybrid control strategy, based on Gao's reaching law and the variable rate reaching law, for practical applications in civil structures by using magnetorheological (MR) dampers. The structure is modeled as a five-degree-of-freedom lumped mass system, controlled by an MR damper placed in between the ground and the first floor. The MR damper is experimentally tested and its behavior is represented by using modified Bouc–Wen model and artificial neural network (ANN) as forward and inverse models, respectively. The five-story building is simulated under the seismic excitation of El Centro earthquake along with the historical earthquake records, Northridge and Kobe. It is demonstrated that the hybrid control strategy yields better results regarding the energy consumption of the controller and time-averaged structural responses by eliminating the chattering, compared to Gao's controller.